Spirituality in business : an investigation into spirituality, spiritual leadership and organisational performance. - Nel, Andre (Stellenbosch : Stellenbosch University, 2011)
Thesis (MBA)--Stellenbosch University, 2008. === ENGLISH ABSTRACT: The integration of spirituality into the workplace is leading to a change in the lives of business leaders and employees. It is becoming evident that spirituality in the workplace is not only having an effect on a personal level through dimensions such as improved well-being, greater connectedness, self-awareness and wholeness, but also improving organisational performance and giving organisations a competitive edge. The objective of this research document is to illustrate the relationship between Spiritual Leadership and positive Organisational Performance. Employees are coming to work for more than just economic prosperity; they are searching for meaning in their work and spiritual leaders need to transform business to enhance not only the well-being of employees and help them with their search for meaning, but also increase their performance excellence. One of the most important new strategic drives for leaders is to be spiritual leaders and therefore create a place of work which provides both a challenging work environment and a work environment which provides a sense of meaning for employees. Spiritual leadership leads to the transformation of the workplace into an environment which incorporates productivity, wholeness, meaning, creativity and connectedness. === AFRIKAANSE OPSOMMING: Die integrasie van spiritualiteit in die werksplek lei tans tot 'n verandering in die lewens van besigheidsleiers en werkememers. Dit is besig om duidelik te word dat spiritualiteit in die werksplek nie net 'n invloed het op 'n persoonlike vlak deur faktore soos verbeterde gesondheid, groter verbondenheid, self-bewustheid en heelheid het nie, maar dat dit ook lei tot 'n verbetering in besigheids prestasie en dat dit besighede 'n kompeterende voordeel kan bied. Die oogmerk van hierdie studie is om die verhouding tussen spirituele leierskap en verbeterde besigheids prestasie toe te lig. Werknemers gaan werk toe op soek na meer as net ekonomiese vooruitgang; hulle is op soek na betekenis in hul werk en die spirituele leier moet besigheid vervorm om nie net die welstand van die werknemer te verbeter en hulle met hul soektog na betekenis te help nie, maar ook werksprestasie verbeter. Een van die belangriskte nuwe strategiese rigtings vir beisgheidsleiers is om spirituele leiers te wees en daardeur 'n werksplek te skep wat beide 'n uitdagende werksomgewing is, sowel as 'n werksomgewing waarin die werknemer betekenis kan vind. Spirituele leierskap lei tot die transformasie van die werksplek tot 'n omgewing wat produktiwiteit, heelheid, betekenis, kreatiwiteit en verbondenheid insluit.